Negative ion enhanced efficient antibacterial polyester fiber and preparation method thereof
By preparing a core-shell structure of composite copolyester and modified tourmaline, the problems of insufficient flame retardancy, antibacterial properties and negative ion release of polyester fibers were solved, achieving highly efficient flame retardant and antibacterial effects while maintaining the toughness of the fibers and uniform release of negative ions.
Patent Information
- Application Number
- CN202511441259.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-10
- Publication Date
- 2025-12-05
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing polyester fibers have shortcomings in terms of flame retardancy, antibacterial properties, and negative ion release, especially the poor durability of flame retardants and the poor compatibility of antibacterial agents, which leads to decreased fiber toughness and uneven release of negative ions.
By preparing a composite copolyester, a stable flame-retardant structure is formed by combining a phosphorus-containing flame retardant with a melamine copolymer. Furthermore, a core-shell structured composite antibacterial agent is formed by copolymerizing silver-coated modified tourmaline with an organic phase, thereby enhancing the flame retardancy and antibacterial properties of the fiber while maintaining its negative ion release capability.
It significantly improves the flame retardant and antibacterial properties of polyester fibers, enhances the release of negative ions, improves the toughness and uniformity of negative ions, and forms a synergistic effect.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of polyester fibers, in particular to a kind of high-efficiency antibacterial polyester fibers with enhanced negative ions and a preparation method thereof. BACKGROUND
[0002] In the field of textile and material science, polyester fibers are widely used in clothing, home textiles, industrial fabrics and other fields due to their high strength, chemical resistance and good processing performance. However, with the expansion of application scenarios and the improvement of safety and health standards, traditional polyester fibers have some shortcomings in flame retardation, antibacterial properties, mechanical properties and functionality.
[0003] During the preparation of polyester, most of the flame retardants are added to improve the flame retardant properties. Although the flame retardant can improve the flame retardant effect, the single phosphorus-based flame retardant has poor compatibility with the matrix and is difficult to be stably combined through covalent bond, resulting in insufficient durability of flame retardant properties. The efficiency of nitrogen-based flame retardant is low when used alone, and an effective synergistic flame retardant system cannot be formed.
[0004] In terms of antibacterial properties, most of the polyester fibers use inorganic antibacterial agents to improve the antibacterial properties. However, inorganic antibacterial agents such as silver ions are prone to agglomeration and loss, and organic antibacterial agents such as quaternary ammonium salts are not firmly combined with fibers, making it difficult to continuously function. In addition, the poor compatibility of inorganic antibacterial agents with the fiber matrix affects the performance of the fiber. The use of conventional flame retardants and inorganic antibacterial agents to modify polyester often leads to a decrease in fiber toughness, and the release of negative ions is unevenly distributed and has a low release amount.
[0005] In summary, it is of great practical significance and urgent need to prepare an antibacterial polyester fiber with high flame retardant properties and high negative ion release. Therefore, a solution is proposed. SUMMARY
[0006] The present application aims to provide a kind of high-efficiency antibacterial polyester fibers with enhanced negative ions and a preparation method thereof, to solve the technical problems that the antibacterial properties, flame retardant properties, toughness and negative ion release of polyester fibers in the prior art need to be further improved.
[0007] The purpose of the present application can be achieved by the following technical scheme: a kind of high-efficiency antibacterial polyester fibers with enhanced negative ions, including the following components by weight: 70-80 parts of polyethylene terephthalate, 15-20 parts of composite copolyester, 2-4 parts of composite antibacterial agent, 0.2-0.5 parts of antioxidant 1010 and 0.5-1 parts of isohexadecane stearate.
[0008] Further, the preparation method of the composite copolyester is as follows: the flame-retardant copolyester, melamine copolymer, polyethylene glycol and catalyst are added into a reaction kettle, the temperature is raised to 260-270℃, and after stirring for 15 min, the reaction is carried out under vacuum for 3-4 h, and the composite copolyester is obtained; the amount ratio of the flame-retardant copolyester, melamine copolymer, polyethylene glycol and catalyst is 3.5 g: 2.8-3.0 g: 3.0-3.2 g: 0.03 g, and the catalyst is diantimony trioxide.
[0009] Reaction principle:
[0010] Under the action of high temperature of 260-270℃ and stirring, the flame-retardant copolyester, melamine copolymer, polyethylene glycol and diantimony trioxide are uniformly mixed, and then the reaction is carried out under vacuum for 3-4 h, under which conditions, the ester group of the flame-retardant copolyester reacts with the amine group in the melamine copolymer, and then the carboxyl group in the melamine copolymer reacts with the hydroxyl group of the polyethylene glycol to form the composite copolyester through ester exchange reaction.
[0011] Further, the flame-retardant copolyester is prepared by the following steps:
[0012] A1, the phosphorus-containing flame retardant, methylene succinic acid and tin tetrachloride are added into a reaction kettle, stirred under nitrogen atmosphere at 150-160℃ for 5-6 h, then acetone is added, and the reaction is carried out at 50℃ for 2-3 h, and then the organic phosphorus-containing compound is obtained after post-treatment;
[0013] A2, the terephthalic acid, ethylene glycol, organic phosphorus-containing compound and catalyst are added into a reaction kettle, stirred under nitrogen atmosphere at 200-220℃ for 3-4 h, then the temperature is raised to 260-270℃ for 3-4 h, and then the flame-retardant copolyester is obtained after post-treatment.
[0014] Reaction principle:
[0015]
[0016] Firstly, 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide reacts with the carbon-carbon double bond in methylene succinic acid through addition reaction under the catalysis of tin tetrachloride and nitrogen atmosphere, and then the organic phosphorus-containing intermediate product with carboxyl group is obtained after purification by acetone; then, the organic phosphorus-containing intermediate product with carboxyl group as a copolymer monomer, together with the carboxyl group of terephthalic acid, is catalyzed by diantimony trioxide to react with the hydroxyl group of ethylene glycol through esterification reaction, and then the reaction is carried out through polycondensation reaction after further heating, so that the flame-retardant copolyester with phosphorus-containing structure in the main chain is finally formed through further connection of ester bonds.
[0017] Further, in step A1, the amount ratio of phosphorus-containing flame retardant, methylenesuccinic acid, tin tetrachloride and acetone is 10.8 g:7-7.5 g:0.03 g:100 mL, the phosphorus-containing flame retardant is 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and the post-treatment operation includes: after the reaction is completed, cooling to room temperature, suction filtration, and washing the product with acetone three times to obtain an organic phosphorus-containing compound; in step A2, the amount ratio of terephthalic acid, ethylene glycol, the organic phosphorus-containing compound and the catalyst is 60-65 g:33 g:5 g:0.02 g, the catalyst is antimony trioxide, and the post-treatment operation includes: after the reaction is completed, cutting under a nitrogen atmosphere, cooling by cold water, and then transferring to a 120℃ vacuum drying oven for drying for 12 h to obtain the flame-retardant copolyester.
[0018] Further, the preparation method of the melamine copolymer is as follows: carboxypropyl-terminated polydimethylsiloxane is added into a reaction kettle, and after being heated to 120-130℃ under a nitrogen atmosphere, melamine powder and p-toluenesulfonic acid are added, and after being heated to 140-150℃ and stirred for 30-40 min, the temperature is continuously increased to 160-180℃ and reacted for 3-4 h, after the reaction is completed, the temperature is cooled to 100-120℃ under a nitrogen atmosphere, the product is discharged, and then transferred to a vacuum drying oven and dried at 80℃ for 2 h to obtain the melamine copolymer; the addition amount of the carboxypropyl-terminated polydimethylsiloxane is 0.35 times the total amount of moles of amino groups in the melamine, and the amount ratio of the melamine and the p-toluenesulfonic acid is 4-5 g:0.2 g.
[0019] Reaction principle:
[0020]
[0021] The carboxypropyl-terminated polydimethylsiloxane is activated under the action of p-toluenesulfonic acid, and melamine is added under a nitrogen atmosphere, and the amino groups and the activated carboxyl groups are preliminarily reacted, and then the temperature is increased, and the amidation reaction is mainly carried out, and the carboxyl groups and the amino groups are dehydrated and condensed to form amide bonds, so that the polydimethylsiloxane chain and the melamine are covalently connected, and finally the residual water is removed by cooling and drying to obtain the melamine copolymer.
[0022] Further, the preparation method of the composite antibacterial agent is: the modified tourmaline is added into deionized water and ultrasonically dispersed for 20-30 min, then methyl acryloyloxyethyl trimethyl ammonium chloride and methyl acrylate are added, stirred for 5-10 min, finally initiator potassium persulfate is added, heated at 60-70 DEG C for 7-8 h, then rotary evaporated for 1-2 h, add acetone, filter the residue, dissolve the residue in deionized water, then add acetone to precipitate, repeat 2-3 times, then transfer the product to a vacuum drying oven and dry at 100 DEG C for 1 h to obtain the composite antibacterial agent; the amount ratio of the modified tourmaline, deionized water, methyl acryloyloxyethyl trimethyl ammonium chloride, methyl acrylate, potassium persulfate and acetone is 10-12 g:100 mL:8-9 g:34 g:0.3 g:80 mL.
[0023] Reaction principle:
[0024] Firstly, the modified tourmaline is ultrasonically dispersed in deionized water to form a uniform dispersion system, then methyl acryloyloxyethyl trimethyl ammonium chloride and methyl acrylate are added and stirred to fully contact with the modified tourmaline, after adding initiator potassium persulfate, heating, the potassium persulfate decomposes to generate free radicals to initiate the free radical copolymerization of the carbon-carbon double bonds of the two monomers, at the same time, the vinyl functional groups on the surface of the modified tourmaline also participate in the polymerization, so that the copolymer is grafted to the surface of the tourmaline through covalent bond to form a composite material with tourmaline as the core and copolymer as the shell, after the reaction, the product is concentrated by rotary evaporation, precipitated by acetone, filtered, then repeatedly purified by multiple dissolution and precipitation, and finally vacuum dried to obtain the composite antibacterial agent.
[0025] Further, the preparation method of the modified tourmaline is:
[0026] B1, silver nitrate is added into anhydrous ethanol and deionized water, stirred until completely dissolved, then ammonia water is added dropwise to adjust the pH of the solution to 8-9 to obtain a silver sol;
[0027] B2, nano tourmaline powder is added into the silver sol, stirred for 15-20 min, then ultrasonically dispersed for 50-60 min, then sodium borohydride solution is slowly added dropwise, continue to stir for 1.5-2 h, then stand for 3-4 h, and finally post-treated to obtain silver-modified tourmaline powder;
[0028] B3, vinyltrimethoxysilane is added into anhydrous ethanol and deionized water, ammonia water is added dropwise to adjust the pH to 7.5-8.5, then the silver-modified tourmaline powder is added and ultrasonically dispersed at 40-50 DEG C for 40-50 min, and finally post-treated to obtain the modified tourmaline.
[0029] Reaction principle:
[0030] Firstly, the silver nitrate is dissolved in the mixed system of anhydrous ethanol and deionized water, then the ammonia water is added dropwise to react with silver ions to form stable silver-ammonia complex ions which are uniformly dispersed in the solution to form silver sol, then the nanometer tourmaline powder is uniformly dispersed in the silver sol, and the sodium borohydride solution is added, the sodium borohydride reduces the silver ions in the silver sol to silver element, the silver element is deposited on the surface of the tourmaline powder to form a silver coating layer, after centrifugation, washing, drying, grinding and sieving, the silver modified tourmaline powder is obtained, finally, the vinyltrimethoxysilane is added into the mixed system of anhydrous ethanol and deionized water, and hydrolysis reaction occurs under the action of ammonia water, the trimethoxysilane group is converted into silicon hydroxyl group, then the silicon hydroxyl group reacts with the hydroxyl group on the surface of the silver coated tourmaline powder to form silicon oxygen bond, so that the vinyltrimethoxysilane is grafted to the surface of the tourmaline through covalent bond, and the modified tourmaline with vinyl functional group on the surface is obtained after centrifugation, washing and drying.
[0031] Further, in step B1, the amount ratio of silver nitrate, anhydrous ethanol and deionized water is 10-12g:50mL:100mL, and the concentration of ammonia water is 0.1mol / L; in step B2, the amount ratio of nanometer tourmaline powder, silver sol and sodium borohydride solution is 10g:100-150mL:8-10mL, the sodium borohydride solution is obtained by dissolving 0.38g of sodium borohydride in 100mL of ice water, and the post-treatment operation includes: after the reaction is completed, centrifugal separation is performed, the product is washed with deionized water for 2-3 times, then washed with anhydrous ethanol once, then transferred to a vacuum drying oven, dried at 60℃ for 12h, then ground and sieved through a 200 mesh screen to obtain the silver modified tourmaline powder; in step B3, the amount ratio of vinyltrimethoxysilane, anhydrous ethanol, deionized water and silver modified tourmaline powder is 4-6g:50mL:250mL:20g, the concentration of ammonia water is 0.1mol / L, and the post-treatment operation includes: after the reaction is completed, centrifugal separation is performed, the product is washed with anhydrous ethanol for 2-3 times, then transferred to a vacuum drying oven, dried at 60℃ for 2h to obtain the modified tourmaline.
[0032] The preparation method of the negative ion enhanced high-efficiency antibacterial polyester fiber comprises the following steps:
[0033] S1, respectively, polyethylene terephthalate and composite copolyester chips are added to a mixer and mixed for 2-3 minutes, then isohexadecyl stearate is added and mixed for 2-3 minutes, then a composite antibacterial agent is added and mixed for 3-5 minutes, and finally antioxidant 1010 is added and mixed for 2-3 minutes to obtain a mixture;
[0034] S2, the double screw extruder is warmed up, each section reaches the set temperature and is kept for 10 min, then the mixture is put into the double screw extruder, melt blending for 3-5 min, the melt is extruded, cooled by 20-30 DEG C cold water, cut into particles, and transferred to a vacuum drying box for drying at 80 DEG C for 4 h, to obtain polyester material;
[0035] S3, the polyester material is added to a single screw spinning machine for melting, the melt is extruded through a spinneret, enters a side blowing cooling device for cooling, is guided out through a godet, enters a heat setting roller, and is set for 30-60 s, to obtain high-efficiency antibacterial polyester fiber.
[0036] Further, in step S2, the temperature of the eight temperature zones of the double screw extruder arranged from the feeding end to the die head is set as 240 DEG C, 250 DEG C, 260 DEG C, 270 DEG C, 270 DEG C, 280 DEG C, 270 DEG C, and 280 DEG C in sequence; and in step S3, the temperature of the eight temperature zones of the single screw spinning machine arranged from the feeding end to the spinneret is set as 250 DEG C, 260 DEG C, 270 DEG C, 280 DEG C, 280 DEG C, 290 DEG C, 280 DEG C, and 290 DEG C in sequence.
[0037] The present application has the following advantages:
[0038] 1. The flame-retardant copolyester of the present application generates an organic phosphorus-containing compound through the addition reaction of a phosphorus-containing flame retardant and methylene succinic acid, and then copolymerizes with terephthalic acid and ethylene glycol, thereby stably introducing phosphorus elements into the polyester main chain to construct a flame-retardant basic skeleton; the melamine copolymer forms a flexible segment of a nitrogen-containing flame-retardant group through amidation reaction of carboxypropyl-terminated polydimethylsiloxane and melamine; and when the two are reacted to generate a composite copolyester under the catalysis of antimony trioxide, the ester group of the flame-retardant copolyester is combined with the amine group of the melamine copolymer, and the carboxyl group of the melamine copolymer is subjected to ester exchange with the hydroxyl group of polyethylene glycol, thereby forming a stable structure with both rigid skeleton and flexible connection, realizing the synergistic flame-retardant effect of phosphorus and nitrogen elements, and significantly improving the flame-retardant performance of polyester fiber.
[0039] 2. The modified tourmaline of the present application is first coated with silver sol, so that elemental silver is deposited on the surface to form a silver ion antibacterial base, and then modified by vinyltrimethoxysilane to introduce a vinyl functional group, thereby enhancing the compatibility with organic phases; in the preparation of the composite antibacterial agent, the vinyl group of the modified tourmaline participates in the free radical copolymerization of methacryloyloxyethyl trimethylammonium chloride and methyl acrylate, thereby forming a core-shell structure with tourmaline as the core and an antibacterial copolymer as the shell; the silver ion continuously sterilizes through slow release, and the quaternary ammonium salt group destroys the bacterial cell membrane through charge effect, thereby realizing synergistic antibacterial effect; at the same time, the copolymer shell layer can reduce the loss of silver ions to prolong the service life, thereby effectively enhancing the antibacterial performance of polyester fiber.
[0040] 3、The flexible chain segment of polyethylene glycol in the composite copolyester of the application balances with the rigid skeleton of the flame-retardant copolyester and melamine copolymer, alleviates the weakening of the flame-retardant component on toughness, stearic acid isohexadecyl ester as a lubricant improves the interfacial compatibility of melt processing, reduces stress concentration, makes plastic deformation more likely to occur when the fiber is stretched, the surface structure of the nano tourmaline powder is not damaged after being coated with silver and modified with silane, and the negative ion release capacity is still maintained, the core-shell structure of the composite antibacterial agent ensures its uniform dispersion in the fiber, avoids agglomeration to affect the release efficiency, and through the element and structure synergy of the composite copolyester and the composite antibacterial agent, the breaking elongation of the polyester fiber and the negative ion generation amount are simultaneously improved. DETAILED DESCRIPTION
[0041] The technical solutions of the application will be described clearly and completely below in combination with the embodiments. Obviously, the described embodiments are only part of the embodiments of the application, rather than all the embodiments. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor fall within the protection scope of the application.
[0042] In the application, polyethylene terephthalate is selected from Dongguan Jin Plastic Yan Plastic Co., Ltd., and the model number is 3267.
[0043] In the application, polyethylene glycol is selected from Dezhou Zhonghe Chemical Co., Ltd., and the CAS number is 25322-68-3, and the model number is PEG200.
[0044] In the application, carboxypropyl-terminated polydimethylsiloxane is selected from Shanghai Yuan Ye Biological Technology Co., Ltd., and the CAS number is 158465-59-9, and the article number is T21796.
[0045] In the application, nano tourmaline powder is selected from Hangzhou Zheming New Material Co., Ltd., and the effective ingredient content is 99%, and the average particle size is 30 nm.
[0046] Example 1
[0047] The embodiment provides a negative ion enhanced high-efficiency antibacterial polyester fiber and a preparation method thereof, and the method comprises the following steps.
[0048] S1, preparing a flame-retardant copolyester
[0049] Weighing: 21.6g 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 14g methylene succinic acid and 0.1g tin tetrachloride are added to a reaction kettle, stirred at 150℃ under a nitrogen atmosphere for 5h, then 200mL of acetone is added, and the reaction is incubated at 50℃ for 2h, after the reaction is completed, the temperature is cooled to room temperature, and the product is washed with acetone for 3 times, to obtain an organic phosphorus-containing compound;
[0050] Take: 120 g terephthalic acid, 66 g ethylene glycol, 10 g organic phosphorus compound and 0.04 g antimony trioxide into the reaction kettle, stir for 3 h at 200℃ under nitrogen atmosphere, continue to heat to 260℃ for 3 h, after the reaction is completed, cut into particles under nitrogen atmosphere, cool by cold water, then transfer to 120℃ vacuum drying oven and dry for 12 h, to obtain the flame-retardant copolyester.
[0051] S2, preparation of melamine copolymer
[0052] Take: the addition amount of carboxypropyl-terminated polydimethylsiloxane calculated as 0.35 times the total amino molar amount in melamine into the reaction kettle, heat to 120℃ under nitrogen atmosphere, then add 8 g melamine powder and 0.4 g p-toluenesulfonic acid, heat to 140℃ and stir for 30 min, then continue to heat to 160℃ and react for 3 h, after the reaction is completed, cool to 100℃ under nitrogen atmosphere, discharge, and transfer to a vacuum drying oven and dry at 80℃ for 2 h to obtain the melamine copolymer.
[0053] S3, preparation of composite copolyester
[0054] Take: 7 g flame-retardant copolyester, 5.6 g melamine copolymer, 6 g polyethylene glycol and 0.06 g antimony trioxide into the reaction kettle, heat to 260℃, stir for 15 min, then react under vacuum for 3 h, and discharge to obtain the composite copolyester;
[0055] S4, preparation of modified tourmaline
[0056] Take: 20 g silver nitrate into 100 mL anhydrous ethanol and 200 mL deionized water, stir until completely dissolved, then add 0.1 mol / L ammonia water dropwise to adjust the solution pH to 8 to obtain silver sol;
[0057] Take: 0.38 g sodium borohydride is dissolved in 100 mL ice water to obtain a sodium borohydride solution;
[0058] Take: 20 g nano tourmaline powder into 200 mL silver sol, stir for 30 min, then ultrasonic dispersion for 50 min, then slowly add 16 mL sodium borohydride solution dropwise, continue to stir for 1.5 h, then stand for 3 h, after the reaction is completed, centrifugal separation, wash the product with deionized water for 2 times, then wash with anhydrous ethanol for 1 time, transfer to a vacuum drying oven and dry at 60℃ for 12 h, then grind and pass through a 200 mesh sieve to obtain silver-modified tourmaline powder;
[0059] Weighing: 8 g of vinyl trimethoxysilane is added to 100 mL of anhydrous ethanol and 500 mL of deionized water, 0.1 mol / L of ammonia water is added dropwise to it until the pH is 7.5, stirred for 5 min, then 40 g of silver-modified tourmaline powder is added, ultrasonic dispersion is carried out at 40°C for 40 min, after the reaction is completed, centrifugal separation is carried out, the product is washed with anhydrous ethanol for 2 times, and then transferred to a vacuum drying oven, dried at 60°C for 2 h, to obtain the modified tourmaline.
[0060] S5, preparation of a composite antibacterial agent
[0061] Weighing: 20 g of modified tourmaline is added to 200 mL of deionized water and ultrasonic dispersed for 20 min, then 16 g of methacryloyloxyethyl trimethyl ammonium chloride and 68 g of methyl acrylate are added, stirred for 5 min, and finally 0.6 g of initiator potassium persulfate is added, heated at 60°C for 7 h, then rotary evaporated for 1 h, 160 mL of acetone is added, filtered, then the filter residue is dissolved in deionized water, and then precipitated by adding acetone, repeated for 2 times, then the product is transferred to a vacuum drying oven, dried at 100°C for 1 h, to obtain the composite antibacterial agent.
[0062] S6, preparation of high-efficiency antibacterial polyester fiber
[0063] Weighing: 70 parts of polyethylene terephthalate and 15 parts of composite copolyester chips are weighed, added to a mixer, mixed for 2 min, then 0.5 parts of isohexadecyl stearate is added, mixed for 2 min, then 2 parts of the composite antibacterial agent is added, and mixed for 3 min, finally 0.2 parts of antioxidant 1010 is added, mixed for 2 min, to obtain the mixture;
[0064] The temperature of the eight temperature zones of the twin-screw extruder from the feeding end to the die head is set to 240°C, 250°C, 260°C, 270°C, 270°C, 280°C, 270°C, and 280°C, respectively, and after the temperature of each section reaches the set temperature, the mixture is added after being kept for 10 min, and the melt is blended for 3 min, then the melt is extruded, cooled by cold water at 20°C, cut into particles, and transferred to a vacuum drying oven, dried at 80°C for 4 h, to obtain the polyester material;
[0065] The polyester material is added to a single-screw spinning machine, and the temperature of the eight temperature zones of the single-screw spinning machine from the feeding end to the spinneret is set to 250°C, 260°C, 270°C, 280°C, 280°C, 290°C, 280°C, and 290°C, respectively, and after the polyester material is melted, the melt is extruded through the spinneret, enters the side-blowing cooling device for cooling, and then enters the hot setting roller, and is set for 30 s, to obtain the high-efficiency antibacterial polyester fiber.
[0066] Example 2
[0067] The embodiment provides a kind of negative ion enhanced high-efficiency antibacterial polyester fiber and its preparation method, comprising the following steps:
[0068] S1, preparing flame-retardant copolyester
[0069] Take: 21.6g 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 14.5g methylene succinic acid and 0.1g tin tetrachloride are added to the reaction kettle, stirred at 150°C under nitrogen atmosphere for 5.5h, then 200mL acetone is added, and incubated at 50°C for 2.5h.After the reaction is completed, it is cooled to room temperature, filtered, and the product is washed with acetone 3 times to obtain an organic phosphorus-containing compound;
[0070] Take: 125g terephthalic acid, 66g ethylene glycol, 10g organic phosphorus-containing compound and 0.04g antimony trioxide are added to the reaction kettle, stirred at 210°C under nitrogen atmosphere for 3.5h, then continue to heat to 260°C and react for 3.5h, after the reaction is completed, cut into particles under nitrogen atmosphere, cool by cold water, then transfer to a 120°C vacuum drying oven and dry for 12h to obtain the flame-retardant copolyester.
[0071] S2, preparing melamine copolymer
[0072] Take: the addition amount of carboxypropyl-terminated polydimethylsiloxane calculated according to 0.35 times the total amino molar amount in melamine is added to the reaction kettle, heated to 120°C under nitrogen atmosphere, then 9g melamine powder and 0.4g p-toluenesulfonic acid are added thereto, heated to 140°C and stirred for 30min, then continue to heat to 160°C and react for 3.5h, after the reaction is completed, cool to 110°C under nitrogen atmosphere, discharge, transfer to a vacuum drying oven and dry at 80°C for 2h to obtain the melamine copolymer.
[0073] S3, preparing composite copolyester
[0074] Take: 7g flame-retardant copolyester, 5.8g melamine copolymer, 6.2g polyethylene glycol and 0.06g antimony trioxide are added to the reaction kettle, heated to 260°C, stirred for 15min, then react under vacuum environment for 3.5h, and discharge to obtain the composite copolyester;
[0075] S4, preparing modified tourmaline
[0076] Take: 22g silver nitrate is added to 100mL anhydrous ethanol and 200mL deionized water, stirred until completely dissolved, then 0.1mol / L ammonia water is added dropwise to adjust the pH of the solution to 8.5 to obtain silver sol;
[0077] Take: 0.38g sodium borohydride is dissolved in 100mL ice water to obtain a sodium borohydride solution;
[0078] Weighing: 20 g of nanometer tourmaline powder is added to 250 mL of silver sol, stirred for 15 min, and then ultrasonically dispersed for 50 min. Then 18 mL of sodium borohydride solution is slowly added dropwise. After continuous stirring for 1.5 h, it is left to stand for 3.5 h. After the reaction is completed, centrifugal separation is performed. The product is washed twice with deionized water and once with anhydrous ethanol. Then it is transferred to a vacuum drying oven and dried at 60℃ for 12 h. After grinding and passing through a 200 mesh sieve, silver-modified tourmaline powder is obtained.
[0079] Weighing: 10 g of vinyltrimethoxysilane is added to 100 mL of anhydrous ethanol and 500 mL of deionized water. Then 0.1 mol / L of ammonia water is added dropwise until the pH is 8. After stirring for 5 min, 40 g of silver-modified tourmaline powder is added and ultrasonically dispersed at 40℃ for 40 min. After the reaction is completed, centrifugal separation is performed. The product is washed twice with anhydrous ethanol. Then it is transferred to a vacuum drying oven and dried at 60℃ for 2 h to obtain modified tourmaline.
[0080] S5, Preparation of composite antibacterial agent
[0081] Weighing: 22 g of modified tourmaline is added to 200 mL of deionized water and ultrasonically dispersed for 20 min. Then 17 g of methacryloyloxyethyl trimethyl ammonium chloride and 68 g of methyl acrylate are added. After stirring for 5 min, 0.6 g of initiator potassium persulfate is added. After heating at 60℃ for 7.5 h, rotary evaporation is performed for 1.5 h. Then 160 mL of acetone is added. After filtration, the filtrate is dissolved in deionized water and precipitated by adding acetone. After repeating twice, the product is transferred to a vacuum drying oven and dried at 100℃ for 1 h to obtain a composite antibacterial agent.
[0082] S6, Preparation of high-efficiency antibacterial polyester fiber
[0083] Weighing: 75 parts of polyethylene terephthalate and 17 parts of composite copolyester chips are added to a mixer and mixed for 2 min. Then 0.8 parts of isohexadecyl stearate is added and mixed for 2 min. Then 3 parts of composite antibacterial agent is added and mixed for 4 min. Finally, 0.3 parts of antioxidant 1010 is added and mixed for 2 min to obtain a mixture.
[0084] The temperatures of the eight temperature zones of the twin-screw extruder from the feeding end to the die head are set as 240℃, 250℃, 260℃, 270℃, 270℃, 280℃, 270℃, and 280℃, respectively. After heating to the set temperature of each section and maintaining for 10 min, the mixture is fed into the extruder. The melt is blended for 4 min and then extruded. The melt is cooled by cold water at 25℃, pelletized, and then transferred to a vacuum drying oven and dried at 80℃ for 4 h to obtain polyester material.
[0085] The polyester material is added to a single screw spinning machine, and the temperature of the eight temperature zones arranged from the feeding end to the spinneret of the single screw spinning machine is set to 250℃, 260℃, 270℃, 280℃, 280℃, 290℃, 280℃, and 290℃ in sequence. After the polyester material is melted, the melt is extruded through the spinneret, enters the side-blowing cooling device for cooling, is guided out by the godet, enters the heat setting roller, and is set for 40s to obtain the high-efficiency antibacterial polyester fiber.
[0086] Example 3
[0087] The embodiment provides a negative ion enhanced high-efficiency antibacterial polyester fiber and a preparation method thereof, and the method comprises the following steps:
[0088] S1, preparing a flame-retardant copolyester
[0089] Take 21.6g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 15g of methylene succinic acid and 0.1g of tin tetrachloride into a reaction kettle, stir under a nitrogen atmosphere at 160℃ for 6h, then add 200mL of acetone, and incubate at 50℃ for 3h. After the reaction is completed, cool to room temperature, filter, wash the product with acetone for 3 times, and obtain an organic phosphorus-containing compound.
[0090] Take 130g of terephthalic acid, 66g of ethylene glycol, 10g of the organic phosphorus-containing compound and 0.04g of antimony trioxide into a reaction kettle, stir under a nitrogen atmosphere at 220℃ for 4h, then continue to heat to 270℃ and react for 4h. After the reaction is completed, cut the particles under a nitrogen atmosphere, cool by cold water, and then transfer to a 120℃ vacuum drying oven for drying for 12h to obtain the flame-retardant copolyester.
[0091] S2, preparing a melamine copolymer
[0092] Take the addition amount of carboxypropyl-terminated polydimethylsiloxane calculated according to 0.35 times the total amino molar amount in melamine into a reaction kettle, heat to 130℃ under a nitrogen atmosphere, then add 10g of melamine powder and 0.4g of p-toluenesulfonic acid into the reaction kettle, heat to 150℃ and stir for 40min, then continue to heat to 180℃ and react for 4h. After the reaction is completed, cool to 120℃ under a nitrogen atmosphere, discharge, and transfer to a vacuum drying oven for drying at 80℃ for 2h to obtain the melamine copolymer.
[0093] S3, preparing a composite copolyester
[0094] Take 7g of the flame-retardant copolyester, 6g of the melamine copolymer, 6.4g of polyethylene glycol and 0.06g of antimony trioxide into a reaction kettle, heat to 270℃, stir for 15min under a vacuum environment, and react for 4h to obtain the composite copolyester.
[0095] S4, Preparation of modified tourmaline
[0096] Weighing: 24g of silver nitrate was added to 100mL of anhydrous ethanol and 200mL of deionized water, stirred until completely dissolved, then 0.1mol / L of ammonia water was added dropwise to adjust the solution pH to 9, to obtain a silver sol;
[0097] Weighing: 0.38g of sodium borohydride was dissolved in 100mL of ice water to obtain a sodium borohydride solution;
[0098] Weighing: 20g of nano tourmaline powder was added to 300mL of silver sol, stirred for 20min, then ultrasonic dispersed for 60min, then 20mL of sodium borohydride solution was slowly added, continued to stir for 2h, then stand for 4h, after the reaction was completed, centrifugal separation, the product was washed with deionized water 3 times, then washed with anhydrous ethanol once, transferred to a vacuum drying oven, dried at 60℃ for 12h, then ground and passed through a 200 mesh sieve to obtain silver modified tourmaline powder;
[0099] Weighing: 12g of vinyl trimethoxysilane was added to 100mL of anhydrous ethanol and 500mL of deionized water, 0.1mol / L of ammonia water was added dropwise to a pH of 8.5, stirred for 10min, then 40g of silver modified tourmaline powder was added, ultrasonic dispersed at 50℃ for 50min, after the reaction was completed, centrifugal separation, the product was washed with anhydrous ethanol 3 times, transferred to a vacuum drying oven, dried at 60℃ for 2h to obtain modified tourmaline.
[0100] S5, Preparation of composite antibacterial agent
[0101] Weighing: 24g of modified tourmaline was added to 200mL of deionized water and ultrasonic dispersed for 30min, then 18g of methacryloyloxyethyl trimethyl ammonium chloride and 68g of methyl acrylate were added, stirred for 10min, finally 0.6g of initiator potassium persulfate was added, heated at 70℃ for 8h, then rotary evaporated for 2h, added 160mL of acetone, filtered, then the filter residue was dissolved in deionized water, then precipitated with acetone, repeated 3 times, then the product was transferred to a vacuum drying oven, dried at 100℃ for 1h to obtain a composite antibacterial agent.
[0102] S6, Preparation of high-efficiency antibacterial polyester fiber
[0103] Weighing: 80 parts of polyethylene terephthalate and 20 parts of composite copolyester chips were weighed, added to a mixer and mixed for 3min, then 1 part of isohexadecyl stearate was added, mixed for 3min, then 4 parts of composite antibacterial agent was added, continued to mix for 5min, finally 0.5 parts of antioxidant 1010 was added, mixed for 3min to obtain a mixture;
[0104] The temperature of the eight temperature zones of the twin-screw extruder arranged from the feeding end to the die head was set as 240℃, 250℃, 260℃, 270℃, 270℃, 280℃, 270℃, 280℃, respectively. After the temperature of each section reached the set temperature, the mixture was added into the extruder, and the melt blending was carried out for 5 min. The melt was cooled by 30℃ cold water, and then was dried in a vacuum drying oven at 80℃ for 4 h to obtain the polyester material.
[0105] The polyester material was added into the single-screw spinning machine. The temperature of the eight temperature zones of the single-screw spinning machine arranged from the feeding end to the spinneret was set as 250℃, 260℃, 270℃, 280℃, 280℃, 290℃, 280℃, 290℃, respectively. After the polyester material was melted, the melt was extruded through the spinneret, and then was cooled by the side-blowing cooling device. After being guided by the godet, the melt was introduced into the heat setting roller, and was set for 60 s to obtain the high-efficiency antibacterial polyester fiber.
[0106] Comparative Example 1
[0107] The difference between this comparative example and Example 3 was that steps S2 and S3 were cancelled, and the flame-retardant copolyester prepared in step S1 was used to replace the composite copolyester in step S6.
[0108] Comparative Example 2
[0109] The difference between this comparative example and Example 3 was that steps S1 and S3 were cancelled, and the melamine prepared in step S2 was used to replace the composite copolyester in step S6.
[0110] Comparative Example 3
[0111] The difference between this comparative example and Example 3 was that step S4 was cancelled, and no modified tourmaline was added in step S5.
[0112] Comparative Example 4
[0113] The difference between this comparative example and Example 3 was that step S5 was cancelled, and the modified tourmaline prepared in step S4 was used to replace the composite antibacterial agent in step S6.
[0114] Performance test:
[0115] The antibacterial rate of the high-efficiency antibacterial polyester fiber prepared in Examples 1-3 and Comparative Examples 1-4 against Escherichia coli and Staphylococcus aureus was determined according to the standard GB / T 20944.3-2008 “Evaluation of antibacterial properties of textiles Part 3: oscillation method”.
[0116] The limiting oxygen index of the high-efficiency antibacterial polyester fiber prepared from Examples 1-3 and Comparative Examples 1-4 was determined according to the standard FZ / T 50016-2023 "Chemical fiber - Test method for combustion performance - Oxygen index method";
[0117] The elongation at break of the high-efficiency antibacterial polyester fiber prepared from Examples 1-3 and Comparative Examples 1-4 was determined according to the standard GB / T 14344-2022 "Chemical fiber - Test method for filament tensile properties";
[0118] The negative ion generation amount of the high-efficiency antibacterial polyester fiber prepared from Examples 1-3 and Comparative Examples 1-4 was determined according to the standard GB / T 30128-2013 "Textiles - Detection and evaluation of negative ion generation", and the specific test results are shown in Table 1 below:
[0119] Table 1 - Performance test data table of the sample
[0120]
[0121] Data analysis:
[0122] Comparative analysis of the data in Table 1 above, the high-efficiency antibacterial polyester fiber prepared by the present application has a bacteria inhibition rate of 99.8% for E. coli and 99.7% for S. aureus, a limiting oxygen index of 47.5%, an elongation at break of 42.4%, and a negative ion generation amount of 887 / cm 3 ;
[0123] The limiting oxygen index of the examples is 46.7-47.5%, which is significantly higher than that of Comparative Example 1 and Comparative Example 2, because in the examples, the flame-retardant copolyester introduces phosphorus elements into the polyester main chain to construct a rigid flame-retardant skeleton, and the melamine copolymer provides a flexible chain segment containing nitrogen, and when the two are reacted with polyethylene glycol under catalysis to form a composite copolyester, a stable structure of "rigid skeleton-flexible connection" is formed through ester group and amine group combination, carboxyl and hydroxyl ester exchange, realizing the synergistic flame-retardant effect of phosphorus and nitrogen elements, while Comparative Example 1 only uses flame-retardant copolyester and Comparative Example 2 only uses melamine copolymer, lacking phosphorus-nitrogen synergy and structure complementation, so the flame-retardant performance is weak;
[0124] The antibacterial rate of the embodiment on E. coli and S. aureus is more than 99%, which is much higher than that of Comparative Example 3 and Comparative Example 4, because in the embodiment, the modified tourmaline is coated with silver to form a silver ion antibacterial base, and then the vinyl group is introduced by silane modification to copolymerize with the monomer containing quaternary ammonium salt, forming a core-shell structure with tourmaline as the core and antibacterial copolymer as the shell. The silver ion slow-release sterilization and the quaternary ammonium salt destruction of the bacterial cell membrane form a synergy, and the copolymer shell layer reduces the loss of silver ions. Comparative Example 3 does not add modified tourmaline, and Comparative Example 4 only uses modified tourmaline to replace the composite antibacterial agent, lacking the synergistic effect of quaternary ammonium salt and the stabilizing effect of copolymer, so the antibacterial effect is greatly reduced.
[0125] The elongation at break of the embodiment is 41.6-42.4%, which is higher than that of Comparative Example 2, Comparative Example 4 and Comparative Example 1, because in the embodiment, the flexible segment of polyethylene glycol in the composite copolyester balances the rigid skeleton of the flame-retardant copolyester and melamine copolymer, alleviating the weakening of the flame-retardant component on toughness, and the isocetyl stearate as a lubricant improves the interfacial compatibility of melt processing, reducing stress concentration. Comparative Example 2 only uses melamine copolymer, and Comparative Example 4 does not use a composite antibacterial agent, so the fiber is more prone to brittle fracture when stretched, and the elongation at break is lower.
[0126] The amount of negative ions generated by the embodiment is 865-887 / cm 3 , which is significantly higher than that of Comparative Example 3, because in the embodiment, the nano-tourmaline powder is coated with silver and modified with silane, and the surface structure is not damaged, still maintaining the ability to release negative ions, and the core-shell structure of the composite antibacterial agent ensures its uniform dispersion in the fiber, avoiding agglomeration to hinder the release of negative ions. Comparative Example 3 does not add modified tourmaline, losing the negative ion release carrier, so the amount of negative ions generated is greatly reduced.
[0127] The preferred embodiments of the application disclosed above are only used to help explain the application. The preferred embodiments do not describe all the details and limit the application to the specific embodiments. Obviously, many modifications and changes can be made according to the content of the specification. The embodiments are selected and described in detail in order to better explain the principles and practical applications of the application, so that those skilled in the art can well understand and utilize the application. The application is limited by the claims and their entire scope and equivalents.
Claims
1. A high efficiency antibacterial polyester fiber enhanced by negative ions, characterized in that, It comprises the following components by weight: 70-80 parts of polyethylene terephthalate, 15-20 parts of composite copolyester, 2-4 parts of composite antibacterial agent, 0.2-0.5 parts of antioxidant 1010 and 0.5-1 parts of isohexadecane stearate.
2. The anion-enhanced high-efficiency antibacterial polyester fiber according to claim 1, characterized in that, The preparation method of the composite copolyester is: adding flame-retardant copolyester, melamine copolymer, polyethylene glycol and catalyst into a reaction kettle, heating to 260-270 DEG C, stirring for 15 min, then reacting for 3-4 h under vacuum environment, discharging to obtain the composite copolyester; the amount ratio of the flame-retardant copolyester, melamine copolymer, polyethylene glycol and catalyst is 3.5 g: 2.8-3.0 g: 3.0-3.2 g: 0.03 g, and the catalyst is diantimony trioxide.
3. The anion enhanced high efficiency antibacterial polyester fiber according to claim 2, characterized in that, The flame-retardant copolyester is prepared by the following steps: A1, adding phosphorus-containing flame retardant, methylene succinic acid and tin tetrachloride into a reaction kettle, stirring for 5-6 h under nitrogen atmosphere at 150-160 DEG C, then adding acetone, reacting for 2-3 h under 50 DEG C, and post-treating to obtain an organic phosphorus-containing compound; A2, adding terephthalic acid, ethylene glycol, the organic phosphorus-containing compound and catalyst into a reaction kettle, stirring for 3-4 h under nitrogen atmosphere at 200-220 DEG C, then continuously heating to 260-270 DEG C and reacting for 3-4 h, and post-treating to obtain the flame-retardant copolyester.
4. The anion enhanced high efficiency antibacterial polyester fiber according to claim 3, characterized in that, In step A1, the amount ratio of the phosphorus-containing flame retardant, methylene succinic acid, tin tetrachloride and acetone is 10.8 g: 7-7.5 g: 0.03 g: 100 mL, the phosphorus-containing flame retardant is 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and the post-treating operation includes: after the reaction, cooling to room temperature, suction filtration, and washing the product with acetone for 3 times to obtain the organic phosphorus-containing compound; in step A2, the amount ratio of terephthalic acid, ethylene glycol, the organic phosphorus-containing compound and catalyst is 60-65 g: 33 g: 5 g: 0.02 g, the catalyst is diantimony trioxide, and the post-treating operation includes: after the reaction, cutting under nitrogen atmosphere, cooling by cold water, and then transferring to a 120 DEG C vacuum drying box for drying for 12 h to obtain the flame-retardant copolyester.
5. The anion enhanced high efficiency antibacterial polyester fiber according to claim 2, wherein, The preparation method of the melamine copolymer is: adding carboxypropyl-terminated polydimethylsiloxane into a reaction kettle, heating to 120-130 DEG C under nitrogen atmosphere, then adding melamine powder and p-toluenesulfonic acid, heating to 140-150 DEG C, stirring for 30-40 min, continuously heating to 160-180 DEG C, and reacting for 3-4 h, after the reaction, cooling to 100-120 DEG C under nitrogen atmosphere, discharging, and transferring to a vacuum drying box for drying for 2 h under 80 DEG C to obtain the melamine copolymer; the addition amount of the carboxypropyl-terminated polydimethylsiloxane is 0.35 times of the total amount of amino groups in melamine, and the amount ratio of the melamine and p-toluenesulfonic acid is 4-5 g: 0.2 g.
6. The anion enhanced high efficiency antibacterial polyester fiber according to claim 1, wherein, The preparation method of the composite antibacterial agent is: modified tourmaline is added into deionized water and ultrasonic dispersed for 20-30 min, then methyl acryloyloxyethyl trimethyl ammonium chloride and methyl acrylate are added, stirred for 5-10 min, finally initiator potassium persulfate is added, heated at 60-70 DEG C for 7-8 h, then rotary evaporation for 1-2 h, add acetone, filter the residue, dissolve in deionized water, add acetone for precipitation, repeat 2-3 times, then transfer the product to a vacuum drying oven, dry at 100 DEG C for 1 h, to obtain the composite antibacterial agent; the amount ratio of modified tourmaline, deionized water, methyl acryloyloxyethyl trimethyl ammonium chloride, methyl acrylate, potassium persulfate and acetone is 10-12 g:100 mL:8-9 g:34 g:0.3 g:80 mL.
7. The anion enhanced high efficiency antibacterial polyester fiber according to claim 6, characterized in that, The preparation method of the modified tourmaline is: B1, silver nitrate is added into anhydrous ethanol and deionized water, stirred until completely dissolved, then ammonia water is added dropwise to adjust the pH of the solution to 8-9, to obtain silver sol; B2, nano tourmaline powder is added into the silver sol, stirred for 15-20 min, then ultrasonic dispersed for 50-60 min, then sodium borohydride solution is slowly added dropwise, continue to stir for 1.5-2 h, then stand for 3-4 h, post-treatment, to obtain silver modified tourmaline powder; B3, vinyltrimethoxysilane is added into anhydrous ethanol and deionized water, ammonia water is added dropwise to pH 7.5-8.5, stirred for 5-10 min, then silver modified tourmaline powder is added, ultrasonic dispersed at 40-50 DEG C for 40-50 min, post-treatment, to obtain modified tourmaline.
8. The anion enhanced high efficiency antibacterial polyester fiber according to claim 7, characterized in that, In step B1, the amount ratio of silver nitrate, anhydrous ethanol and deionized water is 10-12 g:50 mL:100 mL, the concentration of ammonia water is 0.1 mol / L; in step B2, the amount ratio of nano tourmaline powder, silver sol and sodium borohydride solution is 10 g:100-150 mL:8-10 mL, the sodium borohydride solution is obtained by dissolving 0.38 g of sodium borohydride in 100 mL of ice water, the post-treatment operation includes: after the reaction is completed, centrifugal separation, the product is washed with deionized water for 2-3 times, then washed with anhydrous ethanol once, then transferred to a vacuum drying oven, dried at 60 DEG C for 12 h, then ground, passed through a 200 mesh sieve, to obtain silver modified tourmaline powder; in step B3, the amount ratio of vinyltrimethoxysilane, anhydrous ethanol, deionized water and silver modified tourmaline powder is 4-6 g:50 mL:250 mL:20 g, the concentration of ammonia water is 0.1 mol / L, the post-treatment operation includes: after the reaction is completed, centrifugal separation, the product is washed with anhydrous ethanol for 2-3 times, then transferred to a vacuum drying oven, dried at 60 DEG C for 2 h, to obtain modified tourmaline.
9. The method of preparing anion-enhanced high-efficiency antibacterial polyester fiber according to any one of claims 1-8, characterized in that, The method comprises the following steps: S1, polyethylene terephthalate glycol and composite copolyester chips were respectively added into a mixer and mixed for 2-3 min, then isocetyl stearate was added and mixed for 2-3 min, then the composite antibacterial agent was added and mixed for 3-5 min, finally antioxidant 1010 was added and mixed for 2-3 min to obtain a mixture; S2, the twin-screw extruder was warmed up, and after each section reached the set temperature, it was kept for 10 min, then the mixture was added into the extruder, and the melt was blended for 3-5 min, then the melt was extruded, cooled by cold water at 20-30 ℃, cut into particles, and transferred into a vacuum drying box for drying at 80 ℃ for 4 h to obtain polyester material; S3, the polyester material was added into a single-screw spinning machine for melting, and the melt was extruded through a spinneret, then entered a side-blowing cooling device for cooling, then was introduced through a godet, and then entered a heat setting roller for setting for 30-60 s to obtain high-efficiency antibacterial polyester fiber.
10. The method for preparing a negative ion-reinforced high-efficiency antibacterial polyester fiber according to claim 9, characterized in that, In step S2, the temperatures of the eight temperature zones of the twin-screw extruder arranged from the feeding end to the die head were set as 240 ℃, 250 ℃, 260 ℃, 270 ℃, 270 ℃, 280 ℃, 270 ℃, and 280 ℃, respectively; in step S3, the temperatures of the eight temperature zones of the single-screw spinning machine arranged from the feeding end to the spinneret were set as 250 ℃, 260 ℃, 270 ℃, 280 ℃, 280 ℃, 290 ℃, 280 ℃, and 290 ℃, respectively.